A Critical Overview of Translation" Khiaban-e-Faris" by Maulana Zafar Ali Khan - Arshad, Muhammad Abrar (sourcecoder, 2023)
Maulana Zafar Ali Khan translated the book of Lord Kirzen “The persia and the pession question". In this translation, Maulana Zafar Ali Khan has tried to maintain the actual spirit and sense of the book. It becomes clear from the translation of this book that Maulana Zafar Ali Khan had matchless expertise over Urdu and English language. Maulana Zafar has adopted a smooth and unique style in this translation. He maintained the original sequence, balance and the beauty of the text. The translation of Maulana is full of literary beauty. In order to maintain the intrest and charm in the translation, Maulana adopted the poetic style.